The Charm of Damarwulan: A Symbol of a Hero Shining in the Midst of Darkness (Peirce's Semiotic Study) - Utami, Respati Retno; Supratno, Haris; Darni, Darni (Proceeding of International Joint Conference on UNESA, 2025)
This study focuses on Serat Damarwulan, which is an important symbol in local culture and is often seen as a representation of courage and sacrifice. In the context of Javanese culture, Damarwulan is a symbol of strength and struggle. However, research that examines Serat Damarwulan in the context of the symbol of Damarwulan's charm has not been studied. The novelty of this study is the use of Peirce's semiotics in the symbol of Damarwulan's Charm. Pierce's Semiotic Theory explains that signs have three basic elements, namely representamen, objects, and interpretants. In the context of Serat Damarwulan, representamen can be seen from the shape and physical characteristics of Damarwulan. Objects include various meanings contained in traditions or folklore that connect Damarwulan with the concept of heroism. Interpretant is the meaning that appears in relation to the symbol that is believed. The method used in this study is descriptive qualitative. Data collected through interviews, and literature studies related to Serat Damarwulan. The results of the study show that Serat Damarwulan is not just a physical object, but also contains complex symbolic meanings. Damarwulan is interpreted as a symbol of courage, determination, and hope in the midst of rebellion. This sign serves as a reminder of the struggle of local heroes who inspire future generations to continue fighting in difficult situations. In addition, this research can increase the cultural value of lockl and the identity of Wong Jawa in Serat Damarwulan.